Worldwide forest surveys reveal forty-three new species in Phytophthora major Clade 2 with fundamental implications for the evolution and biogeography of the genus and global plant biosecurity - Jung, T. (2024)
During 25 surveys of global Phytophthora diversity, conducted between 1998 and 2020, 43 new species were detected in natural ecosystems and, occasionally, in nurseries and outplantings in Europe, Southeast and East Asia and the Americas. Based on a multigene phylogeny of nine nuclear and four mitochondrial gene regions they were assigned to five of the six known subclades, 2a-c, e and f, of Phytophthora major Clade 2 and the new subclade 2g. The evolutionary history of the Clade appears to have involved the pre-Gondwanan divergence of three extant subclades, 2c, 2e and 2f, all having disjunct natural distributions on separate continents and comprising species with a soilborne and aquatic lifestyle and, in addition, a few partially aerial species in Clade 2c; and the post-Gondwanan evolution of subclades 2a and 2g in Southeast/East Asia and 2b in South America, respectively, from their common ancestor. Species in Clade 2g are soilborne whereas Clade 2b comprises both soil-inhabiting and aerial species. Clade 2a has evolved further towards an aerial lifestyle comprising only species which are predominantly or partially airborne. Based on high nuclear heterozygosity levels ca. 38 % of the taxa in Clades 2a and 2b could be some form of hybrid, and the hybridity may be favoured by an A1/A2 breeding system and an aerial life style. Circumstantial evidence suggests the now 93 described species and informally designated taxa in Clade 2 result from both allopatric non-adaptive and sympatric adaptive radiations. They represent most morphological and physiological characters, breeding systems, lifestyles and forms of host specialism found across the Phytophthora clades as a whole, demonstrating the strong biological cohesiveness of the genus. The finding of 43 previously unknown species from a single Phytophthora clade highlight a critical lack of information on the scale of the unknown pathogen threats to forests and natural ecosystems, underlining the risk of basing plant biosecurity protocols mainly on lists of named organisms. More surveys in natural ecosystems of yet unsurveyed regions in Africa, Asia, Central and South America are needed to unveil the full diversity of the clade and the factors driving diversity, speciation and adaptation in Phytophthora.